2020
DOI: 10.1002/rcm.8832
|View full text |Cite
|
Sign up to set email alerts
|

Proficiency testing of 78 international laboratories measuring tritium in environmental waters by decay counting and mass spectrometry for age dating and water resources assessment

Abstract: Tritium ( 3 H) is an important hydrological tracer commonly used for over 60 years to evaluate water residence times and water dynamics in shallow/recent groundwaters, streams, lakes and the ocean. We tested the analytical performance of 78 international laboratories engaged in low-level 3 H assays for water age dating and monitoring of environmental waters. METHODS:Seven test waters were distributed by the IAEA to 78 international tritium laboratories. Set 1 included a tritium-free groundwater plus three ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Our data evaluation and assessment for WICO2020 followed the methods described in previous IAEA proficiency tests 1,3,20,21 proficiency tests, we applied a two-fold "coverage factor" to σ p for acceptable laboratory evaluation as reflected in the z-score criteria.…”
Section: Data Evaluationmentioning
confidence: 99%
“…Our data evaluation and assessment for WICO2020 followed the methods described in previous IAEA proficiency tests 1,3,20,21 proficiency tests, we applied a two-fold "coverage factor" to σ p for acceptable laboratory evaluation as reflected in the z-score criteria.…”
Section: Data Evaluationmentioning
confidence: 99%
“…Several examples of tritium applications in South‐America can be mentioned, such of those in hydrological (Martinez et al, 2017), hydrogeological (da Silva et al, 2020; Martinez et al, 2016), or the use of South‐American information for atmospheric applications (Aggarwal et al, 2016). Contemporary natural concentrations (0.5–30 TU) observed in South‐America (Martinez et al, 2017; Silva & Cota, 2021), are often below the detection limit of modern Liquid Scintillation Counters, which is the reason why pre‐concentration via electrolytic enrichment is typically applied (Copia et al, 2020; GNIP, 2021; Östlund & Werner, 1962; Taylor, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…In our analysis we found that 3 H records with at least three years of continuous monthly sampling, whether during the rising or falling limb of the solar cycle, corresponded within the 3 H measurement uncertainty to the stations’ mean value for the period 2008–2018. For our mapping purposes we applied a lower 3 H detection limit cutoff as < 0.5 TU which is in accordance with the lower limit of international laboratory performance 29 but also corresponds to the lowest values of recent GNIP samples analyzed (from Galapagos and Ascension Islands).…”
Section: Methodsmentioning
confidence: 99%
“…2–4 TU. For some regions, like Central America, the Amazon basin, and the large archipelagos in Southeast Asia and the western Pacific, our model predicted 3 H contents < 1 TU in precipitation which is at or below the analytical detection limits of most tritium laboratories 29 , thereby posing significant challenges for practical applications of 3 H as a natural radiotracer for hydrology in these areas. Marine coastal fringes for all continents exhibited lower 3 H in precipitation compared to inland and is clearly influenced by low- 3 H oceanic moisture impacts; yet the continental gradients are not impacted as much as higher latitudes.…”
Section: Unique Global Spatial 3 H Patternsmentioning
confidence: 98%